2016
DOI: 10.1007/s11427-016-0017-3
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive transfer of T cells transduced with a chimeric antigen receptor to treat relapsed or refractory acute leukemia: efficacy and feasibility of immunotherapy approaches

Abstract: Treatment outcomes of acute leukemia (AL) have not improved over the past several decades and relapse rates remain high despite the availability of aggressive therapies. Conventional relapsed leukemia treatment includes second allogeneic hematopoietic stem cell transplantation (allo-HSCT) and donor lymphocyte infusion (DLI), which in most cases mediate, at best, a modest graft-versus-leukemia effect, although their clinical efficacy is still limited. Although allo-HSCT following myeloablative conditioning is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…But it is unlikely to reprogram every physiological role of natural receptors to CARs for disconcerting TME and limited bio-editing technique. Several existing clinical trials with CAR-T cells have reported only transitory and confined antitumor efficacy or some undesirable toxicities including cytokine release syndrome (CRS), "on target/off tumor" recognition, and neurologic toxicities (Bonifant et al, 2016;Ding and Chen, 2016;Neelapu et al, 2018) (Figure 2). Therefore, it is highly necessary how to develop new-generation (NG) CAR constructs capable of bringing superior antitumor activity with minimal toxicity (Figure 3).…”
Section: Future Challenges and Next Generation Designs For Optimizing Car-t Cells Antitumor Achievementsmentioning
confidence: 99%
“…But it is unlikely to reprogram every physiological role of natural receptors to CARs for disconcerting TME and limited bio-editing technique. Several existing clinical trials with CAR-T cells have reported only transitory and confined antitumor efficacy or some undesirable toxicities including cytokine release syndrome (CRS), "on target/off tumor" recognition, and neurologic toxicities (Bonifant et al, 2016;Ding and Chen, 2016;Neelapu et al, 2018) (Figure 2). Therefore, it is highly necessary how to develop new-generation (NG) CAR constructs capable of bringing superior antitumor activity with minimal toxicity (Figure 3).…”
Section: Future Challenges and Next Generation Designs For Optimizing Car-t Cells Antitumor Achievementsmentioning
confidence: 99%
“…Kymriah is the first CAR-T therapy based on CD19 approved by the FDA in 2017 [ 12 ]. Related studies have reported that the complete response rate of CD19-CAR-T cells in hematological malignancies is approximately 88–90% [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chimeric antigen receptor (CAR) T cell therapy is a targeted cellular immunotherapy that uses genetically engineered T cells to specifically eliminate the antigenbearing tumor cells [1][2][3][4][5][6][7]. CAR T therapy has achieved encouraging results in both preclinical and clinical researches of a variety of tumors [7][8][9][10][11][12][13]. It is considered as a revolution in cancer immunotherapy and is leading to a paradigm shift in cancer management.…”
Section: Introductionmentioning
confidence: 99%